Paisagens identitárias e praxiológicas de professoras/es de inglês de cursos de Letras do estado de Goiás - Ferreira, Fernanda Caiado da Costa (2023)
This doctoral dissertation, based on 18 narrative interviews conducted with English professors in Language Teacher Education courses in the state of Goiás, aimed to reflect on the identity and praxiological landscapes that resonated in the participants' accounts as they narrated their trajectories, the importance of the English language in their lives, and the various interconnections related to their pedagogical practices. The reflections brought forth in the narratives discussed here can contribute to the professional development of other teachers and professors, as the unique experiences recounted also reflect broader issues concerning the teaching of English, particularly in the Brazilian context. This relationship reflects the epistemological paradox of researching narratives (FREITAS; GHEDIN, 2015), since by examining the praxiologies of each of the participating professors, it was possible to gain a better understanding of our social and historical context. The problematizations proposed here were discussed based on two questions: 1) What discourses and ideologies shape the experiences of University English professors in Language Teacher Education courses in the state of Goiás and influence their identity constructions? 2) How do these professors mobilize these discourses in their trajectories and how they affiliate with or resist to them? Regarding the discourses and ideologies present in the professors' formation trajectories in this research, it is evident that a significant portion of them is marked by an understanding of language as a neutral and abstract system that must be acquired through rules and grammar. This understanding is based on the fact that, when recounting their experiences in regular schools, many pointed out a focus on grammar and translation at the expense of oral development, which, in turn, had to occur in language schools. In language schools, language teaching is based on textbooks that, despite undergoing modifications to include more diversity, are packaged products (JONAS, 2020) that reinforce neoliberal values and sell a sanitized and neutral reality (MAGALHÃES, 2019). However, due to the failure of regular schools to bring interaction into the classroom, these schools became the landscapes that allowed professors to interact and create meaning in another language (URZÊDA FREITAS; PESSOA, 2020). When discussing their praxiologies, the importance of continuous professional development stands out in the professors' statements, as the lack thereof results in the repetition of old models. Many of these professors are influenced by their own learning experiences, which, in the case of English, are closely tied to a hegemonic conception guided by the episteme of the native speaker. In other words, a significant portion of the professors seem to adhere to imported approaches and methods. On the other hand, many professors demonstrate openness to listening, understanding, and seeking new ways of educating that bring their praxiologies much closer to the needs of their students, which, in my understanding, appears to be the path to follow. Not coincidentally, this openness to the new seems to go hand in hand with an ongoing process of professional development. Doing things differently coincides with exposure to new praxiologies that bring to light obscure aspects of modern knowledge that persist in our frameworks. From this perspective, the main reflection that this doctoral dissertation brings forth is that being a teacher means being in constant motion, understanding that this implies being attentive to new ways of living, thinking, and acting in society so that our classrooms can be more aligned with contextual needs, in a constant process of construction and resignification.